2005
DOI: 10.1007/s00705-005-0689-4
|View full text |Cite
|
Sign up to set email alerts
|

A movement protein and three capsid proteins are all necessary for the cell-to-cell movement of apple latent spherical cheravirus

Abstract: Immunoblot analysis of apple latent spherical cheravirus (ALSV)-infected leaves using a polyclonal antibody against the 21 C-terminal amino acids of a 53 K/42 K movement protein (MP) showed that a protein with an Mr of 42 kDa (42KP) is the dominant form found in vivo, which could indicate that the second AUG is used as an initiation codon of a ORF in RNA2. Co-expression of GFP with 42KP in tobacco epidermal cells showed that 42KP is able to facilitate cell-to-cell trafficking of GFP that is expressed in the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…In addition to having characteristics in common with other picornavirales as discussed above (general capsid structure, polyprotein strategy for [28,30,33,34,43]. In the case of comoviruses, nepoviruses and cheraviruses, experimental evidence has been provided indicating that the tubular structures enable cell-to-cell movement of the virus in the plant and that the viral movement protein is a structural component of the tubules [31,32,46,48,49]. The mechanism of cell-to-cell movement has not yet been elucidated for other viruses.…”
Section: Rationale For the Creation Of The Proposed Family Secoviridaementioning
confidence: 99%
“…In addition to having characteristics in common with other picornavirales as discussed above (general capsid structure, polyprotein strategy for [28,30,33,34,43]. In the case of comoviruses, nepoviruses and cheraviruses, experimental evidence has been provided indicating that the tubular structures enable cell-to-cell movement of the virus in the plant and that the viral movement protein is a structural component of the tubules [31,32,46,48,49]. The mechanism of cell-to-cell movement has not yet been elucidated for other viruses.…”
Section: Rationale For the Creation Of The Proposed Family Secoviridaementioning
confidence: 99%
“…ALSV-RNA 1 is 6813 nt long excluding the 3 0 poly(A) tail and has a single open reading frame (ORF) encoding a replication-associated protein of 243 K (Li et al 2000). RNA 2 is 3385 nt long excluding the 3 0 poly (A) tail, and also has a single ORF encoding a 42 K movement protein (MP) on the N-terminal side and three capsid proteins in the C-terminal region (Li et al 2000;Yoshikawa et al 2006). The virus was originally isolated from an apple tree in Japan (Koganezawa et al 1985), and shown to infect apple latently (Ito and Yoshida 1997).…”
Section: Introductionmentioning
confidence: 99%
“…ALSV-based vector was constructed from the infectious cDNA clone of RNA2 (pEALSR2) by duplication of protease cleavage site between the C terminus of MP and the N terminus of Vp25 (Li et al 2004) and have been used for expression of foreign genes and silencing of endogenous genes in plants (Igarashi et al 2009;Li et al 2004;Takahashi et al 2007;Yaegashi et al 2007;Yoshikawa et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…RNA 1 is 6813 nt long excluding the 3 0 poly(A) tail and has a single open reading frame (ORF) encoding a replication-associated protein of 243 K (Li et al 2000). RNA 2 is 3385 nt long excluding the 3 0 poly (A) tail, and also has a single ORF encoding a 42 kDa movement protein (MP) on the N-terminal side and three capsid proteins in the C-terminal region (Li et al 2000;Yoshikawa et al 2006).…”
Section: Introductionmentioning
confidence: 99%